La antropología amazónica de cara a la cuarta revolución industrial - Santos Granero, Fernando (2021)
In this article, which reproduces the keynote talk presented in September 2019 on the occasion of the 50th anniversary of the Amazonian Anthropology course at the Faculty of Social Sciences of the Pontifical Catholic University of Peru, the author proposes that, from the decade of 2010, Amazonian indigenous peoples have been faced with a new wave of change, this time linked to what the economist Klaus Schwab (2016) has called the «fourth industrial revolution». Its objective is not, however, to discuss the advantages and disadvantages of this new industrial revolution, but to explore what are the new directions that Amazonian anthropology could take in the light of this new wave of change. To this end, the author explores six major lines of research, proposing for each of them a series of questions aimed at promoting or guiding future research.